2021
DOI: 10.3390/antiox10020233
|View full text |Cite
|
Sign up to set email alerts
|

ΔMST and the Regulation of Cardiac CSE and OTR Expression in Trauma and Hemorrhage

Abstract: Genetic deletion of 3-mercaptopyruvate sulfurtransferase (MST) is known to result in hypertension and cardiac hypertrophy in older mice, and is associated with increased anxiety-like behaviors. Endogenous hydrogen sulfide (H2S) produced by MST in the mitochondria is also known to be involved in physiological and cellular bioenergetics, and its dysfunction associated with depressive behavior and increased cardiovascular morbidity. Interestingly, early life stress has been shown to lead to a significant loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…Overall, these observations agree well with the fact that atherosclerosis and hypertension are associated with reduced levels of CSE [41]. Wang et al [59] propose that since both H 2 S and OT are able to act via regulation of NO that CSE may be able to mediate cardioprotection by upregulating OTR through the reperfusion injury salvage kinase (RISK) pathway [5,59]. The RISK pathway has been suggested to be the downstream molecular pathway, where H 2 S and OT signaling converge in cardioprotection in atherosclerosis [59].…”
Section: H 2 S and Oxytocin In Cardiovascular Diseasesupporting
confidence: 67%
See 1 more Smart Citation
“…Overall, these observations agree well with the fact that atherosclerosis and hypertension are associated with reduced levels of CSE [41]. Wang et al [59] propose that since both H 2 S and OT are able to act via regulation of NO that CSE may be able to mediate cardioprotection by upregulating OTR through the reperfusion injury salvage kinase (RISK) pathway [5,59]. The RISK pathway has been suggested to be the downstream molecular pathway, where H 2 S and OT signaling converge in cardioprotection in atherosclerosis [59].…”
Section: H 2 S and Oxytocin In Cardiovascular Diseasesupporting
confidence: 67%
“…Recently the gasotransmitter hydrogen sulfide (H 2 S) and the neuroendocrine oxytocin (OT) systems have been shown to interact and play parallel roles in the heart and brain in response to trauma, both physical and psychological [5][6][7][8][9][10]. Trauma can result from either a physical injury or be of psychological origin, the latter being trauma instigated by a deep emotional pain that threatens the integrity of the self [11].…”
Section: Early Life Stress: Definition and Causementioning
confidence: 99%
“…In line with the CSE −/− -related development of arterial hypertension, we showed that CSE −/− mice undergoing pre-traumatic cigarette smoke exposure to induce COPD presented with higher mean arterial pressures (MAP) during the acute phase after blunt chest trauma despite more pronounced metabolic depression as evidenced by reduced capacity to maintain normoglycemia [127]. We previously also showed that CSE expression is crucial for the adaptive response during acute stress situations [128,129]: (i) CSE-expression was inversely related to barrier dysfunction and, hence, the severity of sepsis-induced acute kidney injury (AKI) [130]; (ii) acute stress-related hyperglycemia down-regulated CSE expression, thereby impairing mitochondrial respiration [131]; (iii) CSE −/− mice presented with aggravated post-traumatic acute lung injury (ALI) after pre-traumatic cigarette smoke exposure [127]; (iv) reduced CSE expression was associated with impaired mitochondrial respiration during sepsis-induced acute kidney injury [132]; (v) in resuscitated murine blunt chest trauma and HS, genetic mutation of another, mainly mitochondria-located H 2 S-producing enzyme 3-MST, the deletion of which is associated with hypertension and cardiac hypertrophy in aged mice [133], caused down-regulation of cardiac CSE expression, which coincided with lower activity of the mitochondrial complex IV activity [134]. Therapeutic effects of H 2 S are at least in part related to improved mitochondrial respiratory activity [135][136][137].…”
Section: Figurementioning
confidence: 99%
“…Vitamin B deficiency-induced hyperhomocysteinemia with consecutively reduced endogenous H 2 S availability enhanced chemically induced experimental colitis [178], and ELS/ACE-induced colitis was significantly ameliorated by exogenous H 2 S supplementation [179] (see Figure 3). Moreover, OT [92,96] and H 2 S [180,181] showed comparable protective properties in the cardiovascular system and converge in the reperfusion injury salvage kinase (RISK) pathway, a signaling mechanism that acts via the regulation of NO [54,96,134] (see Figure 4). Our own findings support this interaction between OT (or the OTR) and H 2 S (and the CSE responsible for endothelial H 2 S formation [182]) Both blunt thoracic trauma [183] and hemorrhagic shock [134] were associated with a parallel reduction of OTR and CSE expression in the myocardium in mice (see Figure 5).…”
Section: Interaction Of Oxytocin and Hydrogen Sulfide In Physical And Psychological Traumamentioning
confidence: 99%
See 1 more Smart Citation